Biomimetic Materials as Potential Medical Adhesives – Composition and Adhesive Properties of the Material Coating the Cuvierian Tubules Expelled by Holothuria dofleinii - Peng, Yong Y.; Glattauer, Veronica; Skewes, Timothy D.; White, Jacinta F.; Nairn, Kate M.; McDevitt, Andrew N.; Elvin, Christopher M.; Werkmeister, Jerome A.; Graham, Lloyd D.; Ramshaw, John A.M. (IntechOpen, 2011)
None